2012
DOI: 10.1039/c2lc40241f
|View full text |Cite
|
Sign up to set email alerts
|

Inertial microfluidics in parallel channels for high-throughput applications

Abstract: Passive particle focusing based on inertial microfluidics was recently introduced as a high-throughput alternative to active focusing methods that require an external force-field to manipulate particles. In this study, we introduce inertial microfluidics in flows through straight, multiple parallel channels. The scalable, single inlet and two outlet, parallel channel system is enabled by a novel, high-density 3D PDMS microchannel manufacturing technology, mediated via a targeted inhibition of PDMS polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…3 New applications have since emerged, with inertial focusing in particular, leading to new methods for high-throughput cytometry. [4][5][6][7][8][9][10] More recently, fluid sculpting via inertial flow has been demonstrated through so-called "pillar programming." 11,12 See Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3 New applications have since emerged, with inertial focusing in particular, leading to new methods for high-throughput cytometry. [4][5][6][7][8][9][10] More recently, fluid sculpting via inertial flow has been demonstrated through so-called "pillar programming." 11,12 See Fig.…”
Section: Introductionmentioning
confidence: 99%
“…34 In a low AR (AR < 1) straight microchannel, Hansson et al demonstrated an even higher efficiency (g > 95%) using 10 lm diameter particles. 35 In terms of collecting large cells, a low AR channel is preferred as the target cells can be collected from a single central outlet, rather than from the two side outlets as in high AR microchannels. While these systems offer good performance in filtration of particles, parameters that are critical in downstream cell analysis, such as viability and proliferation of collected cells, are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…All together, the reported straight channel aspect ratio has been limited to 1:3, with the largest side channel being 100 lm and a maximum flow rate of 200 ll/min. 15,21,22 In this work, we introduce flow through u-shaped channels and demonstrate particle focusing into a single and deterministic lateral position that enables effective extraction of the focused stream at more than 20 times higher flow rate compared to straight channels.…”
Section: High Throughput Particle and Cell Filtrationmentioning
confidence: 99%
“…This is in agreement with our previous work in flow through straight channels up to AR 1:3. 22 In both cases, the particles are focused into a single lateral focusing position when exiting the curvature. In flow through straight, square, and rectangular channels, the absence of particles in the corners in AR $ 1:1 suggests that additional lateral migration effects take place near channel walls.…”
Section: A Flow Through Curved Channelsmentioning
confidence: 99%
See 1 more Smart Citation